PENGARUH BIOCHAR DAN PUPUK HIJAU Calopogonium mucunoides TERHADAP PERTUMBUHAN DAN HASIL KEDELAI (Glycine max L. Merril) SERTA MAKROFAUNA TANAH DI GAWANGAN TANAMAN KELAPA SAWIT - Windy Natasha Putri; Nelvia Nelvia; Idwar Idwar (Jurnal Agroteknologi, 2020)
Oil palm plantations in Riau are very extensive and developed on marginal land. The utilization of oil palm plant for soybean cultivation is an alternative to increasing soybean production in Riau, because soybeans are classified as plants that tolerant to shade. The research aimed to study the interaction of biochar and Calopogonium mucunoides green fertilizer on growth and yield of soybeans and diversity of soil macrofauna in inter-rows of oil palm plant. The research was conducted in Pekanbaru, carried out in 7-year-old oil palm plant and soil science laboratory of the Faculty of Agriculture, University of Riau from April-August 2018. The research was done experimentally in a 3x3 factorial form using a completely randomized design (CRD). The first factor is biochar from coconut shell consists of 3 levels (0, 2,5 and 5 ton.ha-1). The second factor is Calopogonium mucunoides green fertilizer consists of 3 levels (0, 2,5 and 5 ton.ha-1). The parameters observed were plant height, pods per plant, percentage of pithy pods, seeds per plant, seed weight per plot, weight of 100 seeds, population density and relative density of soil macrofauna, and diversity index of soil macrofauna. The results showed 2,5 ton.ha-1 biochar followed by 2,5 ton.ha-1 Calopogonium mucunoides green fertilizer increased the number of pods per plant compared to controls. The total individuals and population of soil macrofauna increased at 5 ton.ha-1 biochar followed by 5 ton.ha-1 Calopogonium mucunoides green fertilizer with the family that was often found, namely Scarabaeidae. The diversity index of soil macrofauna is low.